2019
DOI: 10.1186/s12913-019-4178-y
|View full text |Cite
|
Sign up to set email alerts
|

Nursing and midwifery research activity in Arab countries from 1950 to 2017

Abstract: Background Nursing and midwifery research activity is an important indicator of the quality of healthcare services and the status of nursing profession. The main aim of this study was to assess the research activity in nursing and midwifery field in Arab countries. Method The current study implemented bibliometric method using Scopus database. The search strategy used country affiliation or journal name or keywords as a strategy to retrieve the required documents. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 76 publications
(39 reference statements)
1
27
0
Order By: Relevance
“…The use of Scopus as a bibliometric tool was based on the idea that it has a better coverage of journals than other databases such as Web of Science [29,30]. Additionally, Scopus has been used and validated in previously published bibliometric analyses [8,9,18,[31][32][33][34][35][36][37]. Data were collected in March 2019.…”
Section: Data Sourcementioning
confidence: 99%
“…The use of Scopus as a bibliometric tool was based on the idea that it has a better coverage of journals than other databases such as Web of Science [29,30]. Additionally, Scopus has been used and validated in previously published bibliometric analyses [8,9,18,[31][32][33][34][35][36][37]. Data were collected in March 2019.…”
Section: Data Sourcementioning
confidence: 99%
“…We tried to limit the inclusion of false-positive by manually reviewing the title and abstract of each paper, but we could not limit the likelihood of false-negatives. It should be noted that these limitations are common to bibliometric studies [27,[32][33][34]41].…”
Section: Discussionmentioning
confidence: 99%
“…Scopus is also commonly used in bibliometric studies [27,[31][32][33][34]41]. Bibliometric analyses differ from the methodology employed in systematic reviews; the discussion about the typology of reviews could be found elsewhere [20,[41][42][43]. The use of title search is common in bibliometric studies in contrast to the title-abstract-keywords search query [32][33][34]41].…”
Section: Database and Search Strategymentioning
confidence: 99%
See 2 more Smart Citations